Postpartum-Specific Anxiety and Maternal-Infant Bonding: A Predictive Validity Study amongst Italian Women - Chiara Ionio; Giulia Ciuffo; Paul Christiansen; Anna Maria Della Vedova; Victoria Fallon; Maria Francesca Figlino; Marta Landoni; Sergio A. Silverio; Martina Smorti; Alessandra Bramante (MDPI AG, 2024)
The role of anxiety is unknown in relation to postpartum bonding, unlike the well-known detrimental effect that postpartum depression has on the relationship between a mother and child. This study investigates how anxiety affects mother-infant bonding after childbirth, comparing the Italian version of the Postpartum Specific Anxiety Scale (PSAS-IT) with generalized measures of anxiety. Examining 324 non-randomly-selected participants responding to various scales, including the Edinburgh postnatal depression scale (EPDS), generalized anxiety disorder (GAD), postpartum-specific anxiety scale (PSAS-IT), postpartum bonding questionnaire (PBQ), and baby care questionnaire (BCQ-2), initial results suggest a link between certain postpartum anxiety symptoms and attachment problems. Surprisingly, anxiety measured with the PSAS has no direct influence on attachment; however, it is a strong predictor of bonding, even when maternal age, general anxiety, and depression are taken into account, explaining 3% of the variance in scores (β = 0.26, p < 0.001). This emphasizes the importance of early identification and intervention of postpartum anxiety in promoting bonding between mother and child.